The Positive Impact of Product Quality, Price, and, Promotion on Purchasing Decision of Toyota Innova Cars - Ingrid Winardy; Purnama Yanti Purba; Charles Chaniago; Andika Andika (Universitas Pendidikan Ganesha, 2021)
The phenomenon of declining purchasing decisions can be seen from the fact that sales targets have not been achieved, product quality is not good, prices are not competitive, and promotional strategies are not yet attractive. This study aims to analyze the contribution of product quality, price, and promotion factors to the purchase decision of Toyota Innova at PT Perintis Perkasa. This research is a descriptive study using a quantitative approach. This study involved a sample of 131 consumers who were selected using a simple random sampling technique. Data were collected by providing an instrument in the form of a questionnaire. In addition to questionnaires, data were also collected through observation, interviews, and documentation studies. The data that has been collected is then analyzed using multiple linear regression analysis. The results of data analysis showed that the significance obtained was 0.001 (Sig < 0.05). These results indicate that H0 is rejected and Ha is accepted. Based on these results, it can be concluded that, partially and simultaneously, product quality, price, and promotion have a positive and significant contribution to purchasing a car with the Toyota Innova brand at PT Perintis Perkasa.